Prevalence of Acute Poisoning Cases in Tertiary Care Hospital: A Descriptive Cross-sectional Study - Alok Dhungel,; Asim Pandey,; Sohil Neupane,; Samriddhi Parajuli,; Roshan Bhatta,; Sambhav Ojha, (Janaki Medical College Journal of Medical Science, 2025)
Background & Objectives: Poisoning with intention of self-harm is a leading cause for mortality in developing country like Nepal. Higher number of Organophosphate poisoning cases are being reported due to easy accessibility and low cost. Depression and Alcohol use disorder are the most common risk factor associated with intentional suicide. This study aims to quantify the prevalence of acute poisoning in tertiary care setting, identify the most affected age and sex groups, and assess key risk factors for intentional self‑harm. Materials and Methods: This was the cross-sectional study done in tertiary care hospital in Nepal. The study was conducted between 1st September 2022 to 30th March 2023 in patient with poisoning presenting at Emergency Department or the ICU. Convenience sampling was done. Total sample size for the study was 68. Preformed questionnaire was given for data collection and analysis was done in SPSS version 24. Results: The prevalence of organophosphate poisoning was found to be 44.10%. Amongst all cases of poisoning, highest number of poisoning patients were prevalent in patients aged 20-30 (26.5%). Alcohol use disorder was common in male patients with poisoning whereas depressive disorder was common in female patients. Conclusion: Organophosphate self‑poisoning predominates in young Nepali adults, particularly women, underscoring urgent needs for stricter pesticide control and targeted mental‑health support.